몽골의 희토류 자원: 지질학적 특성, 광화작용 및 부존 현황 - 이승열; 이선진 (자원환경지질, 57(6), 2024)
본 연구는 몽골에 부존하는 희토류 광상의 지질학적 특성, 광화작용, 그리고 자원 잠재력을 분석하였다. 몽골의 주요 희토류 광상은 중생대 카보나타이트(carbonatite) 및 고생대 퍼알칼리(peralkaline) 화강암질 암체와 관련되어 형성되었다. 카보나타이트와 관련된 희토류 광상은 주로 몽골 남부 고비-티엔산 열곡대(Gobi-Tien Shan rift zone)의 알칼리 규산염-탄산염암 복합체(alkaline silicate-carbonatite complex) 내에 분포한다. 이러한 복합체는 네펠린 섬장암(nepheline syenite)과 관련 화산암으로 구성되며, 희토류 원소는 주로 바스트네사이트(bastnäsite), 신키사이트(synchysite), 파리사이트(parisite), 인회석(apatite) 등의 광물 형태로 산출된다. 반면, 퍼알칼리 화강암과 관련된 희토류 광상은 주로 몽골 북서부 알타이(Altai) 지역에 위치한다. 이 유형의 광상에서는 희토류 원소가 엘피다이트(elpidite), 모나자이트(monazite), 제노타임(xenotime), 플루오르탄산염 광물(fluorocarbonates) 등의 광물로 산출되며, 마그마 분화 후기 단계에 농집되어 형성된 것으로 해석된다. 몽골에는 경제적 잠재력을 지닌 여러 유망한 희토류 광상이 존재한다. 특히, 데본기 할잔 부룩테이(Khalzan Buregtei) 퍼알칼리 화강암 광상, 중생대 무쉬가이 후닥(Mushgai Khudag) 및 호트고르(Khotgor) 카보나타이트 광상은 상당한 규모의 희토류 자원을 보유하고 있어 주목할 만하다. 몽골에는 아직 탐사되지 않은 잠재적인 희토류 광상이 존재할 가능성이 높다. 따라서 향후 몽골의 희토류 자원 잠재력을 정확하게 평가하기 위해서는 체계적인 정밀 탐사와 함께 광물학적, 암석학적 특성 및 광상 성인에 대한 심도 있는 연구가 필요하다. This study investigates the geological characteristics, ore-forming processes, and mineral resources of rare earth element (REE) deposits in Mongolia. REE deposits in Mongolia are primarily associated with two distinct geological settings: Mesozoic carbonatites and Paleozoic peralkaline granitic rocks. Carbonatite-related deposits are found within alkaline silicate-carbonatite complexes in the Gobi-Tien Shan rift zone of southern Mongolia. These complexes consist of nepheline syenite and their volcanic equivalents. In these carbonatites, REE are mainly associated with bastnäsite, synchysite, parisite, and apatite. REE mineralization linked to peralkaline granitoid rocks is mainly located in the Mongolian Altai region in the northwest. Here, REE is found in minerals like elpidite, monazite, xenotime, and various fluorocarbonates. These minerals typically form during the final stages of magma differentiation. Mongolia hosts several promising rare earth deposits, with three showing significant economic potential: the Devonian Khalzan Buregtei peralkaline granites, and the Mesozoic Mushgai Khudag and Khotgor carbonatites. Many other promising locations have yet to be fully investigated. Further geological investigations and exploration efforts could substantially expand Mongolia's known rare earth element resources. KCI Citation Count: 0